3234 Cell Proliferation and Differentiation in 3D printed Polycarbonate Urethane Porous Scaffolds - Bijan Abar; Alejandro Aalleja; Cambre Kelly; Natalia Von Windheim; Jennifer West; Kenneth Gall (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: The aim of this study is to understand how porosity and collagen filling impact cell proliferation and differentiation in 3D printed scaffolds. METHODS/STUDY POPULATION: 3 groups of scaffolds will be 3D printed using FDM: solid scaffold, porous scaffold and porous scaffold with collagen gel (n=10 for each group) Internal geometries and surface structure will be analyzed using micro CT and Scanning Electron Mi RESULTS/ANTICIPATED RESULTS: We hypothesize that porosity and collagen filler will increase signal from Picogreen assay and ALP assay when normalized to scaffold surface area, indicating enhanced cell proliferation and differentiation. DISCUSSION/SIGNIFICANCE OF IMPACT: 3D printing PCU is a relatively new technique with very little published in the literature. Previous work has focused on the mechanical properties and not the biological response to the polymer. Understanding how to optimize cellular proliferation and differentiation can lead to the development of better implants that will integrate into the host’s structure and facilitate tissue regeneration.